MANAGEMENT OF ACUTE BACTERIAL SIALADENITIS (Case Report) - I Wayan Arya Krishnawan Firdaus; Maharani Laillyza Apriasari (FKG Unlam, 2018)
Background : Sialadenitis is the inflammation of the salivary gland. Predisposing factors for acute sialadenitis include diabetes mellitus, hypothyroidism, renal failure, and Sjögren syndrome. The most common bacterial cause of acute bacterial sialadenitis is Staphylococcus aureus. Purpose : to report the management of Acute bacterial sialadenitis, especially the recommendation antibiotic for treatment of Acute bacterial sialadenitis. Case : Woman, 34 years old, suffered the pain of left buccal especially when she was eating. There was a lowgrade fever. She has been suffering since 3 days ago, but she did not give any drugs. The intra oral examination showed the stenoni of parotid gland was swollen and painful, and erythematous. The purulent discharge often was observed from the duct orifice when the gland was checked by palpation. The patient was diagnosed as Acute Bacterial sialadenitis. Case management : Amoxycillin caplet 500 mg three times a day, Ibuprofen caplet 400 mg three times a day, and oral rinse contains aloevera gargle three times a day for seven days, then the instruction to patient took a lot of rehydration. After seven days, Cefadroxil capsul 500 mg two times a day replaced amoxycillin caplet 500 mg three times a day. Conclusion : It can be concluded that Cephalosporins display superior pharmacokinetics in saliva and cover the spectrum of all bacteria implicated in sialadenitis.